Different effects of main influence factors on household energy consumption in three typical rural villages of China - Ruiliang Yang; Jiangmin He; Sha Li; Wen Su; Yue Ren; Xinyu Li (Energy Reports, 2018)
Three typical rural villages are chosen as study areas to study the different effects of main influence factors on rural household energy consumption using the ordinary least squares (OLS) model and the quantile regression (QR) model. Three typical rural villages include an affluent rural village in the richest province, a well-off rural village in the most energy-rich province and an out-of-poverty rural village in the most population province. The OLS results show family size and household income are significant at the 10 % level in all study areas, while air conditioner and refrigerator are only significant at the 5 % level of the affluent rural village. Family size has a positive effect on energy consumption, while household income has different effect in different areas. The QR results fluctuate around QLS results with large amplitude, indicating a different pattern of the effect of main independent variables on energy consumption using different models. The slopes are significantly different for all study areas at 10% significant level, which shows the distribution heterogeneity in studying the relationships between energy consumption and influence factors. This study is useful to develop more appropriate energy policy according to the main influence factors in different rural villages.
Keywords: 330; Energy consumption; Influence factor; Ordinary least squares (OLS); Quantile regression (QR)